Hospital infection prevention : principles &practices - Khardori, Nancy; Wattal, Chand (Springer, 2014)
The art of medicine becomes science when supported by evidence. The recommended practices of infection prevention are based on scientific and epidemiologic evidence. However, most health care professionals see them as mandates and fail to incorporate them into their routine patient care activities. Thecore goal of this publication is to link the practices to theprinciples they are based on. The expectation is that understanding of the principles willchange thepractices from mandates to "should do" in the minds of health care professionals. This will lead to improvement inhealth care by preventing unintended harm to patients, co-workers and the communities at large. At the same time, the text provides a comprehensive, thorough and up to date information on all aspects of infection prevention in a reader-friendly manner and therefore, will serve as a valuable reference